2019
DOI: 10.1002/brb3.1480
|View full text |Cite
|
Sign up to set email alerts
|

Association between ELP4 rs986527 polymorphism and the occurrence and development of intracranial arachnoid cyst

Abstract: ObjectiveThe association between ELP4 rs986527 polymorphism and the occurrence and development of intracranial arachnoid cyst was studied in this paper.MethodsEighty‐five patients diagnosed with intracranial arachnoid cysts by cerebral computed tomography scan were selected. Sixty‐three healthy volunteers for medical examination in hospitals served as controls. The cognition, depressive symptoms, and the likelihood of headache, dizziness, head trauma history, dementia, depression, and epilepsy were assessed. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…También se han descrito como reacciones inflamatorias subaracnoideas producidas por infecciones, traumatismos, procesos isquémicos, tumores, neurocirugías y hemorragias cerebrales (Choi & Kim, 1998;Matushita et al, 2018;Mustansir et al, 2018), lo cual conduce a una acumulación patológica de LCR que se caracteriza por la presencia de células inflamatorias y depósitos de hemosiderina, los macrófagos secretan factores proinflamatorios como la IL-1β y TNF-α los cuales activan las vías de señalización de las células endoteliales para iniciar la cascada inflamatoria que promueve células y factores inflamatorios, esto dará lugar a un bucle de retroalimentación positiva por liberación de moléculas de adhesión, lo cual exacerba la reacción inflamatoria (Li et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…También se han descrito como reacciones inflamatorias subaracnoideas producidas por infecciones, traumatismos, procesos isquémicos, tumores, neurocirugías y hemorragias cerebrales (Choi & Kim, 1998;Matushita et al, 2018;Mustansir et al, 2018), lo cual conduce a una acumulación patológica de LCR que se caracteriza por la presencia de células inflamatorias y depósitos de hemosiderina, los macrófagos secretan factores proinflamatorios como la IL-1β y TNF-α los cuales activan las vías de señalización de las células endoteliales para iniciar la cascada inflamatoria que promueve células y factores inflamatorios, esto dará lugar a un bucle de retroalimentación positiva por liberación de moléculas de adhesión, lo cual exacerba la reacción inflamatoria (Li et al, 2019).…”
Section: Discussionunclassified
“…Generalmente se han atribuido a un origen congénito a consecuencia de una microdivisión anómala de las membranas aracnoideas durante el desarrollo fetal (Helland & Wester, 2007;Mustansir et al, 2018), sin embargo se ha planteado que este no sería el único mecanismo implicado y que pueden ser secundarios a reacciones inflamatorias originadas por traumatismo craneoencefálico (TCE), hemorragia cerebral, neurocirugías e infecciones gestacionales lo cual conduce a la acumulación patológica de LCR (Choi & Kim, 1998;Li et al, 2019;Matushita et al, 2018;Mustansir et al, 2018), sin embargo, estos casos son excepcionalmente raros y se ha propuesto que es probable que también tengan un origen congénito.…”
Section: Introductionunclassified
“…One study from China reported an association between the elongator protein complex (ELP) 4 rs986527 polymorphism and the clinical features of arachnoid cyst [ 43 ]. ELP 4 is part of the multisubunit (ELP 1-ELP 6) extension complex, which is critical for the regulation of neuronal maturation (including neuronal system growth, development, and guidance) during neurogenesis.…”
Section: Genetic Backgroundmentioning
confidence: 99%